Emotional Atmosphere’s Role on People’s Application of Their Emotional Intelligence in the Fight Against COVID-19 - Nyamai, Dinah Katindi (Frontiers in Sociology, 2022)
Literature frequently alludes to the fact that competencies related with emotional intelligence help people deal with harmful emotional states like anxiety and stress, but limited research if any has focused on influences of the emotional atmosphere on young people’s application of their emotional intelligence in dealing with crisis. This article seeks to provoke debates about the role the hidden curriculum (emotional or social atmosphere) on young people’s application of their emotional intelligence in the fight against crisis like COVID-19. The target population was 617 and Yamane’s sample calculation formula was employed in determining the sample size which was 243. The researcher used two main data collection methods: a closed-ended questionnaire and interview guide with open ended questions to ensure the validity of the research. The validity of the 14-item questionnaire was determined by experts while its reliability was determined using Chronbach’s alpha which gave a reliability coefficient of .91. The clarity of the interview guide items was determined through pilot testing. The results of both quantitative and qualitative indicated that conducive emotional atmospheres increase people’s mastery of their feelings as well as spur one’s capacity to endure discomforts associated with crises. The implication here is that we ignore the power welded by lessons arising from the emotional atmosphere at our peril.